3'-box-dependent processing of human pre-U1 snRNA requires a combination of RNA and protein co-factors. - Uguen, P; Murphy, S (2004)
Using an in vitro system we have recently shown that the 3' ends of human pre-snRNAs synthesized by RNA polymerase II are produced by RNA processing directed by the snRNA gene-specific 3' box. Towards a complete characterization of this processing reaction we have further investigated the in vitro requirements for proper 3' end formation of pre-U1 snRNA. Here we show that the 5' cap plays a stimulatory role and processing requires creatine phosphate. Our results also indicate that the pre-U1 processing activity is heat sensitive and that an RNA component is required. In addition, the exact sequence adjacent to the 3' box influences the position of the pre-U1 3' end produced in vitro. Interestingly, the processing extract active for 3'-box-dependent processing also contains an activity that converts the 3' end of RNA containing the U1 Sm protein binding site and the 3' terminal stem-loop into the mature form.